The Disparities in Punishment for Narcotic Addiction: Does it Reflect the Value of Justice? - Winjaya Laksana, Andri; Musofiana, Ida; Sulchan, Achmad; Osman, Ahmed Kheir; Sanni, Tajudeen (Jurnal Media Hukum, 2000)
Sentencing disparity in narcotics abuse cases reflects an ongoing legal issue concerning the principle of justice in Indonesia. This research aims to analyze the root causes of such disparities and explore ideal law enforcement approaches for narcotics addicts, grounded in the value of justice. Employing a doctrinal legal research method, this study focuses on statutory interpretation, particularly Articles 111, 112, and 127 of Law No. 35 of 2009 on Narcotics. These provisions lack clear normative boundaries, creating interpretative ambiguity among law enforcement officials. The absence of technical guidelines distinguishing narcotics users from dealers contributes significantly to unequal sentencing. Consequently, addicts with minimal evidence may face charges under severe articles, leading to legal uncertainty, injustice, and diminishing public trust in the criminal justice system. The novelty of this study lies in proposing the integration of international best practices within Indonesia’s legal framework to prioritize humanity, legal certainty, and fairness. The study concludes that regulatory reconstruction is necessary through the substantive revision of Articles 111, 112, and 127, to eliminate multi-interpretation and establish clear classifications of narcotics offenders, thus improving both the enforcement of narcotics law and the credibility of the criminal justice system.